Освещенные аквариумы: роман / Софи Бассиньяк - Бассиньяк Софи (Еще раз о любви, 2010)
Экземпляры: СФ-18 (20100914) / Инвентарный номер: 39087 / Цена: 258.06 / Сис.шифр: 84(4Фра) / Авт.знак: Б 27 / ГРНТИ: 17.82.31 / ББК: 84(4Фра)